A Comparative Study of the Salt-free Reactive Dyeing Property of Treated Cotton Fabric with a Chicken-feather Protein Derivative Agent and a Linking Cationic Agent (Journal of Fiber Bioengineering and Informatics, 2014)
Cotton fabric is treated with a chicken-feather protein derivative auxiliary (named WLS-10) and with aself-made linking cationic agent (named WLS), respectively. WLS-10 was prepared with chicken-featherprotein and WLS. The salt-free reactive dyeing properties of the treated cotton fabric were assessedand compared with the untreated cotton fabric dyed with salt. The results show that both the cottonfabrics treated with WLS-10 and WLS dyed without added salt obtained a higher dye uptake (E), colorstrength value (K=S), fixation of adsorbed dye (F) and the total fixation of the original applied dye (T)than untreated cotton fabric dyed with added salt. The treated cotton fabric did not decrease levelnessand color fastness. However the dyeing properties of the WLS-10 treated cotton fabric were better thanthe WLS treated fabric.